2001
DOI: 10.1097/00003086-200110001-00015
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Changes in Cartilage Matrix

Abstract: S153The structure of the extracellular matrix of articular cartilage varies considerably with age. These changes are attributable to variations in molecular abundance and structure, and they can affect all the matrix components, but none more so than the proteoglycans. Some of these changes are attributable to variations in synthesis whereas others are attributable to variations in degradation, some of the changes occur during juvenile development whereas others occur throughout life, and some of the changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
1
14
0
11
Order By: Relevance
“…Biological resurfacing techniques have emerged as a means of restoring the articular surface contour with hyaline (or at least hyaline-like) cartilage [2][3][4][5][6][7][8][9][10][11] . Both clinical and laboratory studies have demonstrated that age is a significant factor in outcomes following these resurfacing procedures 4,12,13 . Resurfacing an articular defect…”
mentioning
confidence: 99%
“…Biological resurfacing techniques have emerged as a means of restoring the articular surface contour with hyaline (or at least hyaline-like) cartilage [2][3][4][5][6][7][8][9][10][11] . Both clinical and laboratory studies have demonstrated that age is a significant factor in outcomes following these resurfacing procedures 4,12,13 . Resurfacing an articular defect…”
mentioning
confidence: 99%
“…Desse modo, a cartilagem depende totalmente da integridade da rede macromolecular que forma a matriz extracelular, sendo o colágeno responsável pela resistência à deformação e os PGs atuando frente as forças de compressão (ROUGHLEY;WHITE, 1980;SCHMIDT et al, 1990).…”
Section: )unclassified
“…A estrutura da matriz extracelular da cartilagem articular varia com a idade (ROUGHLEY, 2001). Mudanças relacionadas com o envelhecimento na composição geral da matriz cartilagínea também resultam em um tecido com menor capacidade para lidar com o estresse mecânico (HULDELMAIER et al, 2001;LOESER, 2000).…”
Section: )unclassified
See 2 more Smart Citations